Comparative adherence and persistence of single-inhaler and multiple-inhaler triple therapies among patients with chronic obstructive pulmonary disease in Japan: a retrospective cohort study - Olivia Massey; Robert Wood; Kieran J Rothnie; TAKEO ISHII; Alexandrosz Czira; Chris Compton; Afisi Ismaila; Sandra Jokšaitė; Lucinda Camidge; Akiko Mizukami; Masao Yarita; Rad Siddiqui; et al. (BMJ Open)
Objectives To evaluate and compare medication adherence and persistence for patients newly initiating single-inhaler triple therapy (SITT) and multiple-inhaler triple therapy (MITT) for chronic obstructive pulmonary disease (COPD) in Japan.Design Retrospective, new-user, active comparator, observational cohort study using inverse probability of treatment weighting.Setting Health insurance claims data from the Medical Data Vision Co., Ltd, hospital claims database.Participants Adults diagnosed with COPD at age ≥40 years newly initiating MITT or SITT (fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) or formoterol fumarate/budesonide/glycopyrronium) from 1 September 2019 to 31 July 2021.Primary and secondary outcome measures The primary outcome was medication adherence compared between patients using SITT and MITT, assessed by the proportion of days covered ≥80%. Secondary outcomes included medication persistence (time from index treatment initiation to discontinuation) compared between patients using SITT and MITT and medication adherence compared before and after the switch in a subgroup of patients switching from MITT to SITT.Results We included 2575 MITT and 2962 SITT users with similar baseline characteristics following weighting. The proportion of adherent patients was significantly greater for SITT versus MITT users at 6 months (19.7% vs 10.2%, p<0.0001), 12 months (6.0% vs 3.8%, p=0.0009) and 18 months (3.8% vs 1.4%, p<0.0001) post-index. Median persistence was also significantly higher for SITT versus MITT users (2.0 vs 1.0 months, p<0.001). Comparing specific SITT versus MITT, the proportion of adherent patients at each time point and median persistence was greater for FF/UMEC/VI. In patients switching from MITT to SITT (n=688), the proportion of adherent patients increased postswitch at the class level and for FF/UMEC/VI specifically.Conclusions Patients with COPD in Japan who were newly initiating SITT had greater medication adherence and persistence compared with those on MITT up to 18 months following initiation.